(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2010)
The problems of definition of parameters of functional assignment radioelectronic apparatus are considered at designing on the basis of the theory hyperbolic-accidental of the phenomena